Sketching as a Methodology for Creative Practice - Newall, Kim (Auckland University of Technology, 2012)
This exegesis is a reflection and classification of work produced as part of a creative practice-based research thesis. It also draws on knowledge gained over 25 years of practice. Thus, the research documented here can be considered as part of a larger research project to develop a new understanding of using sketching as a methodology for creative practice in the post-digital age. Outcomes will be presented through exhibition and a reflective critique of my own hybrid, interactive, public performance-based practice. In the first section, I describe my background and development of my work. In the second section, I introduce several different properties of sketching that are used to contextualize, classify and analyse the research process and the works that have emerged from this. The third section provides the background for ‘Bathing with Elephants’, an exhibition sketch that will be executed near the end of the thesis year. This work is considered to be ‘in formation’ – it is part of a continuous and ongoing inquiry to make sense of my practice.
Keywords: Sketching; Interdisciplinary; Digital performance